2012
DOI: 10.1007/s00418-012-1033-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functional involvement of Thymosin beta-4 in tooth germ development

Abstract: Thymosin beta-4 (Tβ4) is known to be ubiquitously involved in the actin monomer sequestering on the cytoskeleton. Our previous study showed specific temporal and special in situ expression pattern of Tβ4 mRNA in dental epithelial and mesenchymal cells in the developing tooth germ of the mouse lower first molar. In this study, we examined the functional implications of Tβ4 in the developmental course of the mouse lower first molar. An inhibition assay using Tβ4 antisense sulfur-substituted oligodeoxynucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…Tβ4-overexpressing mice show amelogenesis imperfecta due to the reduction in cell polarity caused by the inhibition of actin polymerization that is required for enamel matrix secretion in and migration of presecretory ameloblasts (Cha et al, 2010). In addition, reduction in Runx2 expression by the suppression of Tβ4 mRNA expression inhibits enamel mineralization by downregulating ameloblastin and amelogenin (Kobayashi et al, 2006;Ookuma et al, 2013). Insulin-like growth factor-I (IGF-I) and IGF-II increase enamel deposition by increasing amelogenin and enamelin expression (Catón et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Tβ4-overexpressing mice show amelogenesis imperfecta due to the reduction in cell polarity caused by the inhibition of actin polymerization that is required for enamel matrix secretion in and migration of presecretory ameloblasts (Cha et al, 2010). In addition, reduction in Runx2 expression by the suppression of Tβ4 mRNA expression inhibits enamel mineralization by downregulating ameloblastin and amelogenin (Kobayashi et al, 2006;Ookuma et al, 2013). Insulin-like growth factor-I (IGF-I) and IGF-II increase enamel deposition by increasing amelogenin and enamelin expression (Catón et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Akhter et al, 2005;Ookuma et al, 2013) demonstrated that Tb4, another member of the beta-thymosin family, participates in the morphogenesis of the tooth germ. However, the in situ expression pattern of Tb10 apparently differs from that of Tb4.…”
Section: Discussionmentioning
confidence: 99%
“…The DM was either the "DP and follicle" in the cultured explants showing the normal cap-like tooth germ or the "odontogenic ectomesenchyme" in the explants exhibiting an inhibition of tooth germ development (Figs. 7 and 8) (Takahashi et al, 2010;Ookuma et al, 2013).…”
Section: Tb10 Expression and Function In Tooth Germ Development 879mentioning
confidence: 99%
See 2 more Smart Citations